PENINGKATAN PENGETAHUAN MELALUI EDUKASI ANTIBULLYING PADA REMAJA MENURUT PERMENDIKBUD NOMOR 82 TAHUN 2015: Array - Karlina Sumiari Tangkas; Ketut Eka Larasati Wardana; Ketut Putra Sedana (LPPM STIKes Buleleng, 2023)
Introduction: The problem of bullying is a matter of serious concern not only for those who are victims, but also a big problem for all parties. The tremendous impact of bullying will occur on the perpetrators and victims. The perpetrator will have a strong character and feel that he has power, the victim of bullying will feel anxious, and it can increase towards depression which can end in suicide. Seeing the impact that is likely to occur as well as research data, it is hoped that if students know about bullying in adolescents then all possible risks can be prevented as early as possible so that it can reduce the number of bullying in adolescents. Methods: This research uses quantitative research with a quasi-experimental research design where the approach used is the pretest-posttest one group design. The sampling technique uses a nonprobability sampling technique, namely purposive sampling technique. Results: The level of knowledge of respondents before being given education to respondents with less knowledge was 47.06%, while 32.35% was sufficient and 20.59% lacking. The level of knowledge of respondents after being given education, good knowledge was 79.41%, 20.59% was sufficient and no one had less knowledge. Meanwhile, based on statistical analysis, it is found that if the p value = 0.000 (p <0.005), the null hypothesis is rejected and the alternative hypothesis is accepted. Conclusion: There is an effect of providing education on increasing respondents' knowledge of bullying.